CARE MODEL IN PRIMARY HEALTH CARE: ACCESS AND COMPREHENSIVE CARE DURING THE COVID-19 PANDEMIC - Ros, Carla da; Peres, Aida Maris; Kalinowski, Carmen Elizabeth; Souza, Marli Aparecida Rocha de; Straub, Michele; Montenegro, Livia Cozer; Martins, Maria Manuela (Cogitare Enfermagem, 2023)
Objective: To analyze the care model in Primary Health Care from the perspective of access and comprehensive care. Method: Qualitative research, with data collected from May to December 2021 in each regional health center in the state of Paraná through recorded interviews using a semi-structured script with 26 managers. IRAMUTEQ software was used to process and group the data into five classes. The results were analyzed using dialectical hermeneutics. Results: Two classes showed actions related to the attributes of access and comprehensiveness present in the care model. Actions to increase access included the participation of a multi-professional team to promote comprehensive care and the use of technological resources while maintaining the biomedical model. Final considerations: During the pandemic, there was adaptation and resilience on the part of managers who organized the care model and the inclusion of technological tools to facilitate access and continuity of care.